MIXING VISCOUS LIQUIDS IN SETTLING TANKS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The study adresses the problem of maintaining the operability of settling tanks designed for storing contaminated liquids. The study provided a method of mixing of bottom sludge and a mathematical model for determining initial velocity of outflow from the flat orifice depending on physical, mechanical and rheological parameters of the bottom sludge.